Studies of microbiological contamination of water from dental units in rural dental practices - Sitkowska, Jolanta; Szymańska, Jolanta; Cholewa, Grażyna (Polish Journal of Public Health, 2010)
Introduction. Scientific studies show that the water used in dental practices, which comes from the dental unit is contaminated with microorganisms – bacteria, fungi and protozoa – and may be the potential source of infections in patients and dental staff. Aim. The objective of the study was the determination of the concentration and species composition of mesophilic bacteria present in the water from dental units in rural dental practices, from the aspect of potential health risk for patients and dental staff. Material and methods. The material for the study was the water sampled from 20 dental unit reservoirs placed in rural dental practices in the Lublin Region. Mesophilic bacteria Gram-positive and Gram-negative were cultured on plating medium enriched with 5% sheep blood. Gram-negative rods were isolated and identified with the use of the selective-differential Eosin-Methylene Blue Agar. The identification of the isolated microorganisms was performed by means of the API 20E and API 20NE test technique, and the BIOLOG system. Results. In all water samples the presence of mesophilic Gram-positive and Gram-negative bacteria was observed. The most abundant group were Gram-negative rods of the species Ralstonia pickettii and Sphingomonas paucimobilis, with the frequency of 35% each. In the group of Gram-positive bacteria, Gram-negative rods of the species Cellulomonas cellasea and genus Staphylococcus spp. were most frequently isolated. The total mean concentration of total microorganisms isolated from the water examined was 84,450.75 cfu/ml. Conclusions. The common character of bacteriological contamination and the presence of opportunistic microorganisms in the water used in dental treatment may constitute a potential risk for the health of patients and dental team. It seems necessary to monitor the microbiological contamination of water in dental units – the application of the recommended methods and chemical agents available for the purpose of decontamination.